Integral methods in low-frequency electromagnetics - Doležel, Ivo (Wiley, 2009)
A modern presentation of integral methods in low-frequency electromagneticsThis book provides state-of-the-art knowledge on integral methods in low-frequency electromagnetics. Blending theory with numerous examples, it introduces key aspects of the integral methods used in engineering as a powerful alternative to PDE-based models. Readers will get complete coverage of:The electromagnetic field and its basic characteristicsAn overview of solution methodsSolutions of electromagnetic fields by integral expressionsIntegral and integrodifferential methodsIndirect solutions of electromagnetic fields.